2014
DOI: 10.1038/ncomms5745
|View full text |Cite
|
Sign up to set email alerts
|

Energy-filtered cold electron transport at room temperature

Abstract: Fermi-Dirac electron thermal excitation is an intrinsic phenomenon that limits functionality of various electron systems. Efforts to manipulate electron thermal excitation have been successful when the entire system is cooled to cryogenic temperatures, typically <1 K. Here we show that electron thermal excitation can be effectively suppressed at room temperature, and energy-suppressed electrons, whose energy distribution corresponds to an effective electron temperature of ~45 K, can be transported throughout d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 50 publications
1
44
1
Order By: Relevance
“…The particle must be at the nanometer scale in order to observe Coulomb blockade at room temperature 16,17 except for very special designs. 18 In a practical way, single electron phenomena are detected as a stepwise increase of the current going through the island, upon increase of the applied potential as shown in Figure 1c. In the literature and to the best of our knowledge, two studies describe single charge architectures where one of the electrodes is a semiconductor substrate: Radojkovic et al reported in 1996 Coulomb staircase I-V curves for 3 nm gold aggregates drop-casted directly on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…The particle must be at the nanometer scale in order to observe Coulomb blockade at room temperature 16,17 except for very special designs. 18 In a practical way, single electron phenomena are detected as a stepwise increase of the current going through the island, upon increase of the applied potential as shown in Figure 1c. In the literature and to the best of our knowledge, two studies describe single charge architectures where one of the electrodes is a semiconductor substrate: Radojkovic et al reported in 1996 Coulomb staircase I-V curves for 3 nm gold aggregates drop-casted directly on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…When a wearer puts his legs in the shoes, then due to the flexibility of soft rubber, the shoes can easily grow or shrink and fit into their feet. In the magnetically levitated shoes, superconducting materials are used on the bottom side of the shoes and to protect the passenger from the chill of cryogenic temperature [9] a shielding material, such as lightweight insulator layer can be used between the feet resting layer and superconducting layer. The additional purpose of using such shielding layer is to protect a wearer having either a cardiac pacemaker or other similar gadgets which are prone to be affected by cryogenic environment and superconductivity.…”
Section: Optical Flow Lk Dog Class [8]mentioning
confidence: 99%
“…This feedback scheme could therefore be used to increase the utility of the quantum dot as an energy-filter, e.g. [34,35]. For values θ < π/2, the feedback loop can be used to increase the width of the resonance (not shown).…”
Section: Energy Filtermentioning
confidence: 99%